Redefining Leadership: An Ethnographic Study of Bureaucratic Transformation in Yogyakarta's Aristocratic Society - Purwanti, Tari; Priyadi, Budi Puspo; Musa, Eltom Ishaq Osman (Faculty of Social and Political Sciences - UIN Walisongo Semarang, 2025)
Bureaucratic transformation in an environment steeped in traditional values demands an unconventional approach to leadership. This article examines how an anthropological perspective can explain the leadership transformation of a mayor who redefines his role-from authority figure to public servant-in the context of Yogyakarta's aristocracy. Using ethnographic methods, including participant observation and in-depth interviews, this study addresses three core questions: how leadership operates as a catalyst for bureaucratic transformation in an aristocratic society; what strategies are used to transform bureaucratic norms into public service; and how civil servants respond to such changes. The research findings suggest that culturally grounded leadership can play an important role in reshaping bureaucratic values and practices. The mayor's leadership broke down entrenched hierarchies, fostering a culture of service and accountability within the bureaucracy. These changes were not only administrative but also structural, contributing to more equitable and responsive governance. Ultimately, this research highlights the importance of context-rooted leadership in public sector reform, emphasizing that transformative change will be more sustainable if leadership strategies are aligned with local cultural frameworks.